Ability to Reach Low-Income Smokers Enrolled in a Randomised Controlled Trial Varies with Time of Month. (28th November 2017) - Hawk, Kathryn; Shi, Ruizhi; Weiss, June; Makuch, Robert; Toll, Benjamin; Bernstein, Steven L.
Abstract : Introduction: Because of financial pressures, low-income individuals sometimes run out of cellphone service towards the end of the month. Aims: To determine if the time of month affects ability to reach low-income smokers by telephone. Methods: We reviewed data from a completed trial in the United States of emergency department (ED)-initiated tobacco dependence treatment for low-income smokers at a busy, academic ED in an urban community. We recorded the date of each one-month follow-up call, and divided each month into four time blocks: Week 1, Week 2, Week 3, and Week 4. Results: A total of 2, 049 phone calls were made to reach 769 participants. Of these calls, 677 (33%) resulted in contact; 88% of all participants were contacted. Using generalised estimating equations with Week 4 as reference, the odds of a successful contact at Weeks 1, 2, and 3 were, respectively, 1.52 (95% CI 1.18, 1.96), 1.30 (95% CI 1.01, 1.66), and 1.37 (95% CI 1.07, 1.76). Conclusions: Study participants became progressively difficult to reach. This result may reflect low-income smokers' decreased rates of active telephone service later in the month and suggests a mechanism to improve follow-up rates in future studies of low-income populations.